PENGARUH POSITIONING, DIFERENSIASI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN BUKU MIMPI SEJUTA DOLAR DENGAN PROMOSI SEBAGAI VARIABEL INTERVENING - Dwihapsari, Ester Ratih; Murni, Yanti (L2Dikti Wilayah III, 2018)
Publishers book Gramedia Pustaka Utama is the largest book publisher in Indonesia are located in Jakarta, With the current information technology and supported by the rapid flow of information to force people to have the ability and knowledge to compensate. The purpose of this study was to determine 1). Whether there are significant positioning, differentiation, brand image and promotions directly on purchasing decisions, 2) whether there are significant positioning, differentiation and brand image on purchasing decisions with a promotion to intervening. Test this hypothesis using path analysis (path analysis) with a significant level of 5%. The population is customers who visited the Gramedia Bookstore Regional 1, using accidental sampling technique and approach the proportions in withdrawing a sample of 100 respondents and data collection was done by questionnaire. The results showed that: 1) Directly positioning, differentiation, brand image and promotion of significant positive effect on purchasing decisions 2). Through the promotion seen that positioning, differentiation and brand image did not significantly influence the purchasing decision. Means of quality books, inspirational, reasonable price and reputation of the issuer greatly influence consumers to buy the Million Dollar Dream book in Gramedia bookstore Region 1 while the promotion is done is not very effective.